A COMPREHENSIVE ANALYSIS OF DRUG PRESCRIBING PRACTICES OF DOCTORS AND COMPLETENESS OF PRESCRIPTION IN A GOVERNMENT MEDICAL COLLEGE IN NORTHERN INDIA - KAMALDEEP SINGH; GARIMA BHUTANI; SEEMA RANI; RAHUL SAINI; ARVIND NARWAT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was designed to analyze the drug prescribing practices of doctors and completeness of prescriptions in a government medical college in Northern India. Methods: A total of 2155 prescriptions were evaluated for adequacy of information related to prescribed drugs and completeness of information related to patients and doctors. Results: The weight of the patient was written only in 1.90% prescriptions. The diagnosis was not written on 43.85% prescriptions. A total number of drugs prescribed in all the prescriptions was 6998. The average number of drugs per prescription was found to be 3.25±0.24. Out of these, 64.10% were prescribed by brand names. About 69.14% of drugs were prescribed in the form of tablets. Route of administration was not found to be mentioned for 86.08% drugs. For 53.90% drugs, dose was not mentioned. The name of the prescribing doctor was mentioned in 1.95% prescriptions only. Conclusion: The study revealed that many prescriptions lacked crucial components of information pertaining to the drugs prescribed and the prescribing doctor. There is a vast scope for improvement by the prescribers.